If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3y + 1) + -1(-2y + -6) = 2 Reorder the terms: -1(1 + 3y) + -1(-2y + -6) = 2 (1 * -1 + 3y * -1) + -1(-2y + -6) = 2 (-1 + -3y) + -1(-2y + -6) = 2 Reorder the terms: -1 + -3y + -1(-6 + -2y) = 2 -1 + -3y + (-6 * -1 + -2y * -1) = 2 -1 + -3y + (6 + 2y) = 2 Reorder the terms: -1 + 6 + -3y + 2y = 2 Combine like terms: -1 + 6 = 5 5 + -3y + 2y = 2 Combine like terms: -3y + 2y = -1y 5 + -1y = 2 Solving 5 + -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1y = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = 2 + -5 -1y = 2 + -5 Combine like terms: 2 + -5 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| 4*4+4*4+4-4*4=0 | | x-8.2=-4.2 | | -r^2+6r-5=0 | | x^3-x-2=0 | | p+25=17 | | -r^2+6r-6=0 | | =0.0232x^2-2.28x+60.0 | | 0=x^2-2x-15 | | 4v^2-4v+1=0 | | 4t^2-4t-3=0 | | 4r^2-4t-3=0 | | 12.8x=3.2 | | 3v^2-5v+2=0 | | 274-5x=40x+19 | | 9-9x=63-23x | | 8x+3=15-4x | | 2x=-15-x | | 10x-15=9x-9 | | 4x+6=6x-16 | | 3(x-2)=2x+1 | | 4x+10=8+2x | | 5x+25=65-3x | | 2(5x-8)=3x+5 | | 7x+2=50+x | | 10x=22-x | | y=10+12x-3X^2-2X^3 | | y=10+12x-3X^2-3X^3 | | 2x*2x^3=0 | | -2a^2-ab+b^2=0 | | 6+1.3n=24 | | 5x-8+3x+6=0 | | -(-9j-7w)= |